A new peripheral endothelial function measurement improves prediction of symptomatic coronary artery disease. Issue 6 (June 2020) - Du, Beibei; Si, Daoyuan; Zhao, Dong; Zhao, Yanan; Wagatsuma, Kenji; He, Yuquan; Yang, Ping
Objective: This study aimed to determine whether a peripheral artery volume (PAV) test can improve the predictive value of the age-adjusted Framingham risk score (AFRS) for coronary artery disease (CAD) in symptomatic patients. Methods: A total of 317 consecutive patients who were referred for coronary angiography were prospectively enrolled. Before cardiac catheterization, a PAV test was performed to measure changes in pulsatile blood flow volume following reactive hyperemia. Results: PAV was significantly lower in patients with CAD than in those without CAD (1.21 ± 0.32 vs. 1.50 ± 0.45). Multivariate logistic regression analysis showed that PAV and the AFRS were independent predictors of CAD. Pairwise comparison of receiver operating characteristic curves showed that the predictive power for CAD increased when PAV was incorporated into the AFRS (area under the curve: from 0.76 to 0.80). The net reclassification index was also improved when PAV was added to the AFRS (0.65, 95% confidence interval: 0.44–0.85). Conclusions: Digital endothelial function measurement is an independent predictor of CAD. PAV is potentially useful for identifying patients at high risk for CAD.